DIGITALIZATION OF TRADE ENTERPRISES BUSINESS PROCESSES: TECHNOLOGICAL DETERMINANTS, ROI AND CYBER RISK MANAGEMENT (Development Service Industry Management, 2025)
Digital transformation is an imperative for the retail sector, fundamentally changing the way the value is created and captured through technologies such as artificial intelligence (AI), the Internet of Things (IoT), and cloud architectures. While these tools provide significant operational efficiency gains – including up to 40% improvement in demand forecasting accuracy – realization of this potential is uneven. Measuring the net return on investment (Net ROI) is a pressing scientific and practical challenge, as growing digital risks, especially cyberthreats, can offset all operational benefits, requiring an integrated approach to evaluating investments. The net return on investment (Net ROI) from digitalizing retail business processes is a function not only of technology adoption (Gross ROI), but also of two key endogenous moderators: the organization’s level of digital maturity (DMM) and the effectiveness of its cyber risk management system (Cyber Risk Discount). The study is based on a systematic analysis of the current economic literature, covering quantitative data on the impact of technologies on the operational efficiency of trade and empirical models of digital risk management. Current quantitative data on the impact of dominant technologies (AI, IoT) on key operational indicators of trade is clustered, providing an empirical basis for calculating Gross ROI. The results demonstrate that unintegrated digital solutions (low DMM) reduce potential ROI by 2-3 times, while an immature security posture leads to significant losses of customer trust (82% of customers may abandon the brand) and direct financial losses. The DMM-Risk-ROI model is substantiated, providing a holistic toolkit for assessing the sustainability of digital investments. The DMM-Risk-ROI model allows management to shift cybersecurity investments from a passive expense (compliance) to an active strategic investment necessary to preserve and maximize the net profit gained from digitalization. To increase Net ROI, retail companies must simultaneously invest in technology (AI/IoT), data integration (DMM), and institutional protection (Cyber Risk Management).
Keywords: digitalization; business process; artificial intelligence; digital maturity; cyber risks; cybersecurity; supply chain; roi